Penyuluhan Kesehatan Tentang Penanganan Dan Pertolongan Pertama Pada Perawatan Luka Bakar di Desa Gulo Kecamatan Darul Hasanah Kabupaten Aceh Tenggara - Sri Mala Hayati; Ade Kartika; Ultra Madani (PPNI UNIMMAN, 2024)
In Indonesia, the prevalence of burns according to the Ministry of the Republic of Indonesia in 2013 was 0.7%. It is feared that continuous administration of antibiotics will cause an accumulation of side effects that can be detrimental to health. The goal of on-site first aid is to save lives and prevent pain from getting worse. Burns are characterized by all injuries except third-degree burns, which appear as white or dark brown burned areas on the skin and can cause shock and infection. Community service methods: socialization, dissemination of knowledge, demonstration, implementation, monitoring and evaluation. This activity will be carried out on Monday, April 22 2024 starting at 10.00 WIB in Gulo Village, Darul Hasanah District, Southeast Aceh Regency. There were around 52 people attending. Participants want to take part in activities, participants want to demonstrate first aid management for burns and pre-hospital care, active participants in the question and answer session.